Advances in Experimental Medicine and Biology
DOI: 10.1007/0-387-34134-x_7
|View full text |Cite
|
Sign up to set email alerts
|

gC1qR/p33 Serves as a Molecular Bridge between the Complement and Contact Activation Systems and Is an Important Catalyst in Inflammation

Abstract: The receptor for the globular heads of C1q, gC1qR/p33, is a ubiquitously expressed protein, which is distributed both intracellularly and on the cell-surface protein. In addition to C1q, this molecule also is able to bind several other biologically important plasma ligands, including high-molecular-weight kininogen (HK), factor XII (FXII), and multimeric vitronectin. Previous studies have shown that incubation of FXII, prekallikrein, and HK with gC1qR leads to a zinc-dependent and FXII-dependent conversion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 25 publications
0
40
1
Order By: Relevance
“…gC1qR is thought to be involved in inflammation via its ability to activate the kinin system on EC [43,44]. More recently, in vitro evidence has been obtained to suggest that gC1qR can directly activate the classical complement cascade by recognizing C1q [20]. Despite the ability of purified gC1qR to activate the classical complement pathway, enhanced C4 activation on EC in the present study did not correlate with changes in gC1qR expression.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…gC1qR is thought to be involved in inflammation via its ability to activate the kinin system on EC [43,44]. More recently, in vitro evidence has been obtained to suggest that gC1qR can directly activate the classical complement cascade by recognizing C1q [20]. Despite the ability of purified gC1qR to activate the classical complement pathway, enhanced C4 activation on EC in the present study did not correlate with changes in gC1qR expression.…”
Section: Discussioncontrasting
confidence: 81%
“…gC1qR is present on the EC surface and was recently shown to participate in classical complement pathway activation [20,21]. Compared to baseline, gC1qR expression increased by approximately 60% (n = 6, P<0.05) in response to shear stress, but was unaffected by TS (0.03 puffs/ml).…”
Section: Complement Activation and Depositionmentioning
confidence: 92%
See 1 more Smart Citation
“…The geometry and topography of the three dimensional structure of gC1qR indicates that gC1qR could engage C1q via at least two, if not three, of its globular heads. This could induce the subtle conformational change that is necessary to trigger C1 activation (Ghebrehiwet, Cebada Mora, Tantral, Jesty, and Peerschke 2006). Indeed, recombinant gC1qR has been shown recently to activate C1 ).…”
mentioning
confidence: 99%
“…Previous studies have shown that native gC1qR purified from Raji cell membranes, or highly purified, and enzyme-free recombinant gC1qR can activate the classical pathway as assessed by hemolytic assay or by solid phase ELISA using gC1qR coated plates and monoclonal antiC4d to detect activation Peterson et al, 1997;Ghebrehiwet et al, 2006). Subsequent experiments showed that the binding site(s) for gC1qR and IgG on the C1q molecule may be identical or perhaps overlap with each other (Peterson et al, 1997) since preincubating serum with gC1qR had a diminished hemolytic activity when further incubated with antibody sensitized sheep erythrocytes.…”
Section: Contribution Of Gc1qr To Inflammation 1 Complement Activationmentioning
confidence: 99%